Les retombées de deux projets de recherche-action impliquant une collaboration interprofessionnelle sur le développement des pratiques inclusives au secondaire - Bergeron, Geneviève; Granger, Nancy (Education Sciences & Society - Open Access, 2016)
This article focuses on the challenges of inclusive education in high school. More specifically, it is based on the linking of two action researches who accompany school teams in their efforts to foster learning in regular classes. The issue features challenges encountered by high school teachers and the importance of suggesting trainings for continuing education to involve interprofessional collaboration. After a brief definition of the central concepts, the methodological specificities of the two projects are explained. The core of this article demonstrates the findings on three aspects: reflexive, operatory and identity. Finally, it highlights evidence of interprofessional collaboration to sustain change in inclusive education. Keywords inclusion; continuing education; interprofessionnal collaboration; action research